2017
DOI: 10.3389/fmed.2017.00206
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Biomarkers in Hereditary Angioedema

Abstract: The unpredictable nature of attacks of tissue swelling in hereditary angioedema requires the identification of reliable biomarkers to monitor disease activity as well as response to therapy. At present, one can assess a C4 level (by ELISA) to assist in diagnosis but neither C4 nor C1 inhibitor levels reflect clinical course or prognosis. We will here review a collection of plasma proteins involved in blood coagulation, fibrinolysis, and innate immunity (Figure 1). A main focus is those proteins that are key to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
0
47
1
1
Order By: Relevance
“…Comprehensive studies have identified BK as the principal mediator of vascular leakage in C1-INH-HAE-related swelling attacks ( 10 , 62 ) Circulating levels of BK, markers of endothelial activation, prothrombin fragments, D-dimer ( 63 ), cytokines (e.g., TNF-α and IL-8), as well as neutrophil count and neutrophil-derived factors (e.g., elastase, myeloperoxidase, pentraxin 3) ( 64 ) are increased during attacks compared with symptom-free periods in C1-INH-HAE patients. By contrast, we found that sPLA 2 activity is consistently decreased during attacks and does not correlate with canonical biomarkers of angioedema severity (i.e., cleaved HK) ( 65 ). Whatever the mechanism(s), sPLA 2 is the first mediators so far identified which shows opposite behavior during clinical remission (i.e., increase) and angioedema attacks (i.e., reduction).…”
Section: Discussioncontrasting
confidence: 67%
“…Comprehensive studies have identified BK as the principal mediator of vascular leakage in C1-INH-HAE-related swelling attacks ( 10 , 62 ) Circulating levels of BK, markers of endothelial activation, prothrombin fragments, D-dimer ( 63 ), cytokines (e.g., TNF-α and IL-8), as well as neutrophil count and neutrophil-derived factors (e.g., elastase, myeloperoxidase, pentraxin 3) ( 64 ) are increased during attacks compared with symptom-free periods in C1-INH-HAE patients. By contrast, we found that sPLA 2 activity is consistently decreased during attacks and does not correlate with canonical biomarkers of angioedema severity (i.e., cleaved HK) ( 65 ). Whatever the mechanism(s), sPLA 2 is the first mediators so far identified which shows opposite behavior during clinical remission (i.e., increase) and angioedema attacks (i.e., reduction).…”
Section: Discussioncontrasting
confidence: 67%
“…The present data suggest that C1-INH deficiency does not make the contact system unstable, but rather makes it hypersensitive to plasmin. The place of fibrinolysis as a trigger in kinin-mediated angioedema states remains to be investigated in detail; it has been noted that plasmin can activate FXII in the absence of a contact system-surface ( 38 , 46 ). Tranexamic acid was predictably effective in a subtype of HAE due to a mutation in FXII, although the series is small ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic impasses described above highlight the absence of biological markers to identify the key mediator of AE. Different diagnostic strategies have been proposed such as: 21,[62][63][64][65] • For MC-AE: Tryptase, D-Dimers, urinary histamine and methylhistamine excretion; • For BK-AE: VE-Cadherin, HWK cleavage, plasma kallikrein activity, C4a.…”
Section: Challenging Idiopathic Non-mc-ae (Inmc-ae)mentioning
confidence: 99%